ANALYSIS OF METHODS OF REGENERATION OF WASTE OILS - A. F. Khuzhakulov; K. Sh. Khotamov (Journals Park Publishing, 2023)
This paper provides an analysis of the methods of regeneration of waste oils. To solve the problems of preventing environmental pollution and import-substituting environmentally safe lubricating oils based on local raw materials with the involvement of additives of vegetable origin.
Keywords: mineral oils, waste oils, raw materials, additive, impurities, coagulation, chemical analysis, temperature greases, regeneration, adsorption.